Anthropogenic Asian aerosols provide Fe to the North Pacific Ocean - Pinedo-González, Paulina (Proc Natl Acad Sci U S A, 2020)
Fossil-fuel emissions may impact phytoplankton primary productivity and carbon cycling by supplying bioavailable Fe to remote areas of the ocean via atmospheric aerosols. However, this pathway has not been confirmed by field observations of anthropogenic Fe in seawater. Here we present high-resolution trace-metal concentrations across the North Pacific Ocean (158°W from 25°to 42°N). A dissolved Fe maximum was observed around 35°N, coincident with high dissolved Pb and Pb isotope ratios matching Asian industrial sources and confirming recent aerosol deposition. Iron-stable isotopes reveal in situ evidence of anthropogenic Fe in seawater, with low δ(56)Fe (−0.23‰ > δ(56)Fe > −0.65‰) observed in the region that is most influenced by aerosol deposition. An isotope mass balance suggests that anthropogenic Fe contributes 21–59% of dissolved Fe measured between 35° and 40°N. Thus, anthropogenic aerosol Fe is likely to be an important Fe source to the North Pacific Ocean.